Surgery plus adjuvant radiotherapy for primary central nervous system lymphoma. (1st November 2020) - Kinslow, Connor J.; Rae, Ali I.; Neugut, Alfred I.; Adams, Christopher M.; Cheng, Simon K.; Sheth, Sameer A.; McKhann, Guy M.; Sisti, Michael B.; Bruce, Jeffrey N.; Iwamoto, Fabio M.; Sonabend, Adam M.; Wang, Tony J. C.
Abstract: Objective: Recent studies of primary central nervous system lymphoma (PCNSL) have found a positive association between cytoreductive surgery and survival, challenging the traditional notion that surgery is not beneficial and potentially harmful. However, no studies have examined the potential added benefits of adjuvant treatment in the post-operative setting. Here, we investigate survival in PCNSL patients treated with surgery plus radiation therapy (RT). Methods: The Surveillance, Epidemiology, and End-Results Program was used to identify patients with PCNSL from 1995–2013. We retrospectively analyzed the relationship between treatment, prognostic factors, and survival using case-control design. Treatment categories were compared to biopsy alone. Results: We identified 5417 cases. Median survival times for biopsy alone ( n  = 1824, 34%), biopsy + RT ( n  = 1460, 27%), surgery alone ( n  = 1222, 27%), and surgery + RT ( n  = 911, 17%) were 7, 8, 20, and 27 months, respectively. On multivariable analysis, surgery + RT was associated with improved survival over surgery alone (hazard ratio [HR] = 0.58 [95% confidence interval = 0.53–0.64] vs. HR = 0.71 [0.65–0.77]). Adjuvant RT was associated with improved survival, regardless of the extent of resection. HR's for subtotal resection, gross-total resection, subtotal resection + RT, and gross-total resection + RT were 0.77 (0.66–0.89), 0.66 (0.57–0.76), 0.62 (0.52–0.72), and 0.54 (0.46–0.63), respectively. Survival improved after adjuvant RT in patients under and over 60 years old. All findings were confirmed by multivariable analysis of cause-specific survival. Conclusion: Adjuvant RT was associated with improved survival in PCNSL patients who underwent surgery. Although these data are hypothesis-generating, additional information on neurotoxicity, dosing, and concurrent chemotherapy will be necessary to validate these findings. Cytoreductive surgery for PCNSL is common in the general population, and more studies are needed to assess optimal treatment in the post-operative setting.